To complete the square for the quadratic equation \( y = x^2 - 16x + 14 \), we follow these steps:
-
Identify the coefficient of \( x \): Here, the coefficient of \( x \) is \(-16\).
-
Take half of that coefficient and square it: \[ (-16/2)^2 = (-8)^2 = 64 \]
-
Add and subtract this square inside the equation: \[ y = (x^2 - 16x + 64) - 64 + 14 \]
-
Rewrite the equation: The expression \( x^2 - 16x + 64 \) can be factored as \( (x - 8)^2 \). \[ y = (x - 8)^2 - 64 + 14 \] \[ y = (x - 8)^2 - 50 \]
-
Identify the vertex: The vertex form of a quadratic equation \( y = a(x - h)^2 + k \) shows that the vertex is at the point \( (h, k) \). In our equation:
- \( h = 8 \)
- \( k = -50 \)
Thus, the vertex of the parabola described by the equation \( y = x^2 - 16x + 14 \) is at the point \( (8, -50) \).
Therefore, the correct answer is: D) (8, −50).